The structure of global management consulting firms - Boussebaa, Mehdi (Henry Stewart Talks, 2015)
Background on global management consulting firms (GMC’s), Archetypal organizational study, The challenge in serving global clients, Culture of reciprocity and global integration, The economic problem of GMC’s